Advances in Human Factors and Systems Interaction Proceedings of the AHFE 2017 International Conference on Human Factors and Systems Interaction, July 17−21, 2017, The Westin Bonaventure Hotel, Los Angeles, California, USA (Advances in Intelligent Systems and Computing,, 2018)
This book reports on cutting-edge research into innovative system interfaces, emphasizing both lifecycle development and human-technology interaction, especially in virtual, augmented and mixed-reality systems. It describes advanced methodologies and tools for evaluating and improving interface usability and discusses new models, as well as case studies and good practices. The book addresses the human, hardware, and software factors in the process of developing interfaces for optimizing total system performance, particularly innovative computing technologies for teams dealing with dynamic environments, while minimizing total ownership costs. It also highlights the forces currently shaping the nature of computing and systems, including the need for decreasing hardware costs; the importance of portability, which translates to the modern tendency toward hardware miniaturization and technologies for reducing power requirements; the necessity of a better assimilation of computation in the environment; and social concerns regarding access to computers and systems for people with special needs. The book, which is based on the AHFE 2017 International Conference on Human Factors and System Interactions, held on July 17-21, 2017, in Los Angeles, California, USA, offers a timely survey and practice-oriented guide for systems interface users and developers alike. .